KOMUNIKASI ANTARBUDAYA MAHASISWA MALAYSIA DAN INDONESIA FAKULTAS DAKWAH DAN KOMUNIKASI UNIVERSITAS ISLAM NEGERI (UIN) SUMATERA UTARA - Insi Luthfiyah Siregar, Syukur Kholil, Mailin (Al-Balagh : Jurnal Komunikasi Islam, 2017)
Abstract: The purpose of this study is to examine intercultural communication between Malaysian and Indonesian students at Faculty of Da'wah and Communication of State Islamic University (UIN) ". In particular, this study aims to find out the interaction between Malaysian and Indonesian students, the respective perceptions between Malaysian and Indonesian students. As well as to know the supporting and inhibiting factors in realizing harmonious relations between Malaysian and Indonesian students at the Faculty of Da'wah and Communications of State Islamic University (UIN) North Sumatra. This research methodology is qualitative research by searching, analyzing and making interpretation of data found through the results of documents, interviews and observations. that has been collected checked the validity through the validity of data in the form of trust. analysis techniques are to reduce, present, and make conclusions of research results. The result of this research is the intercultural communication between Malaysian and Indonesian students in the Faculty of Da’wah and Communications of State Islamic University (UIN). It is not effective from intercultural communication communication between Malaysian and Indonesian students in UIN SU Communication and Communication Faculty, interacting with the need only because they are difficult to adapt, and familiarize themselves with the new environment which they face. This intercultural communication intercultural interaction is rare between two individuals or groups between the two different cultures. The intercept between Malaysian and Indonesian students in da'wah and communication faculty of UIN SU is contradictory between the two, among others, concerning the attitude that exists in both cultures, as well as summarizing the things that exist between the students, which gives rise to prejudices between the two cultures. A person in which he judges and concludes a person's behavior so as to generate perceptions of their respective internal perceptions and external perceptions, with supporting factors, mutual respect, a sense of sportsmanship, as well as inhibiting factors, economics, food, cultural differences, open, lack of togetherness.Tujuan penelitian ini secara umum adalah untuk mengkaji komunikasi antarbudaya mahasiswa Malaysia dan Indonesia di Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN)‛. Secara khusus penelitian ini bertujuan untuk mengetahui interaksi komunikasi antarbudaya mahasiswa Malaysia dan Indonesia, persepsi masing-masing antara mahasiswa Malaysia dan Indonesia. Serta untuk mengetahui faktor pendukung dan penghambat dalam mewujudkan hubungan yang harmonis antara mahasiswa Malaysia dan Indonesia di Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Sumatera Utara. Metodologi penelitian ini merupakan penelitian kualitatif dengan mencari, menganalisis dan membuat interprestasi data yang ditemukan melalui hasil dokumen, wawancara dan pengamatan. Hasil dari penelitian ini adalah komunikasi antarbudaya mahasiswa Malaysia dan Indonesia di Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) ternyata tidak efektif hal ini terapatdariInteraksi komunikasi antarbudaya mahasiswa Malaysia dan Indonesia di fakultas dakwah dan komunikasi UIN SU, berinteraksi dengan seperlunya saja, karena mereka sulit beradaptasi, dan membiasakan diri dengan lingkungan baru yang mereka hadapi. Interaksi komunikasi antarbudaya budaya ini jarang terjadi antara dua individu atau kelompok antara kedua budaya yang berbeda tersebut. Sehingga hubungan antarbudaya keduanya tidak harmonis dan komunikasi yang terjalin kurang efektif.Persepsi masing-masing antara mahasiswa Malaysia dan Indonesia di fakultas dakwah dan komunikasi UIN SU adalah saling bertolak belakang antarkeduanya, diantaranya adalah menyangkut sikap yang ada dalam diri kedua budaya, serta menyimpulkan hal-hal yang menimbulkan prasangka antarkedua budaya tersebut. Seseorang dimana ia menilai dan menyimpulkan perilaku seseorang sehingga menimbulkan persepsi masing-masing yaitu persepsi internal dan persepsi ekternal, dengan faktor pendukung, saling menghargai, rasa percayadansikap sportif, serta faktor penghambat, ekonomi, makanan, perbedaan budaya, saling terbuka, kurangnya kebersamaan.Kata kunci: Komunikasi antar Budaya, Prsepsi, dan Mahasiswa Malaysia dan Indonesia